How sociocultural influences impact young women‘s body image. - Mentzer, Jennifer Kay (Kansas State University, 2011)
Young women are influenced by a variety of different messages as they are transitioning from being viewed as little girls to being viewed as young women. While women of all ages can experience dissatisfaction with their bodies and appearance, this is especially common during the time when girls are entering into adolescence, adjusting to their changing bodies, and trying to develop a sense of who they are as an individual. Our society today has placed a significant importance on thinness and young women are bombarded with messages presenting them with an unattainable level of thinness as society‘s ideal. This paper describes adolescent development, looks at the sociocultural influences (family, peers, and media) that impact young women‘s body image, presents prevention and intervention programs that have been used with young women, and provides recommendations for family life educators on how to educate parents on the messages their daughters are being sent and provides them with suggestions on how to talk with their daughters about these messages.
Keywords: Body image; Adolescents; Media; Peers; Families; Eating disorders; Mental Health (0347); Social Sciences Education (0534)